CARTOGRAFIAS E NARRATIVAS DAS EDUCAÇÕES AMBIENTAIS E ECOLOGIAS INSUBMISSAS NOS COTIDIANOS DAS MULHERES NA BACIA DO RIO FORMATE, VIANA (ES) - Santos, Edilene Machado dos (2020)
This study on environmental education aims to discuss and map teaching strategies on environmental education performed by communities and social movements from Viana. The subjects of this history and participants of this research are activist women from V